(untitled) (Jurnal Mekanikal, 2018)
The growing concern over increasing regional and local emissions and concentrations of nitrogen oxides has led to action to reduce emissions by the introduction of legislation in many countries. Recently, there have been significant developments in nitrogen oxides control legislation, both nationally and internationally. All of these legislation and regulation limits on NOx emissions has led to the development of low NOx combustors especially for new plants. Basically there are two methods of reducing NOx The first involved modifications to the combustion processes to prevent the formation of NOx The second methods is to treat the combustion gas chemically, aji er the flame, to redu ce NOx to N2